The imitative basis of ancient architectural design - Wilson Jones, Mark (Aesthetica Preprint, 2024)
Copying is a loaded term that is best avoided in favour of imitation, which has a basis in Greek philosophy and embraces transformation and invention. To understand the workings of imitation some distinctions are important, even if they overlap: between the aims of evocation and emulation, and between design based on exemplars as opposed to principles. Evidence from Greek and Roman antiquity shows that straightforward repetition was rare. Instead, flexible principles underpinned the classical ethos of sameness-but-difference, and the capacity to generate fresh variations of familiar forms, themes and types.